Stature and mitigation systems affect the risk of leg injury in vehicles attacked under the body by explosive devices - Rebelo, Eduardo A; Grigoriadis, Grigoris; Carpanen, Diagarajen; Bull, Anthony M. J.; Masouros, Spyros (Frontiers in Bioengineering and Biotechnology, 2023)
A finite-element (FE) model, previously validated for underbody blast (UBB) loading, was used here to study the effect of stature and of mitigation systems on injury risk to the leg. A range of potential UBB loadings was simulated. The risk of injury to the leg was calculated when no protection was present, when a combat boot (Meindl Desert Fox) was worn, and when a floor mat (IMPAXXTM), which can be laid on the floor of a vehicle, was added. The risk of injury calculated indicates that the floor mat provided a statistically significant reduction in the risk of a major calcaneal injury for peak impact speeds below 17.5 m/s when compared with the scenarios in which the floor mat was not present. The risk of injury to the leg was also calculated for a shorter and a taller stature compared to that of the nominal, 50th percentile male anthropometry; shorter and taller statures were constructed by scaling the length of the tibia of the nominal stature. The results showed that there is a higher risk of leg injury associated with the short stature compared to the nominal and tall statures, whereas the leg-injury risk between nominal and tall statures was statistically similar. These findings provide evidence that the combat boot and the floor mat tested here have an attenuating effect, albeit limited to a range of possible UBB loads. The effect of stature on injury has implications on how vehicle design caters for all potential anthropometries and indeed gender, as women, on average, are shorter than men. The results from the computational simulations here complement laboratory and field experimental models of UBB, and so they contribute to the improvement of UBB safety technology and strategy.